Activation of the inflammatory transcription factor nuclear factor interleukin-6 during inflammatory and psychological stress in the brain - Fuchs, Franziska; Damm, Jelena; Gerstberger, Rudiger; Roth, Joachim; Rummel, Christoph; Justus Liebig University Giessen (My University, 2013)
BACKGROUND:The transcription factor nuclear factor interleukin 6 (NF-IL6) is known to be activated by various inflammatory stimuli in the brain. Interestingly, we recently detected NF-IL6-activation within the hypothalamus-pituitary-adrenal (HPA)-axis of rats after systemic lipopolysaccharide (LPS)-injection. Thus, the aim of the present study was to investigate whether NF-IL6 is activated during either, inflammatory, or psychological stress in the rat brain. METHODS:Rats were challenged with either the inflammatory stimulus LPS (100mug/kg, i.p.) or exposed to a novel environment. Core body temperature (Tb) and motor activity were monitored using telemetry, animals were killed at different time points, brains and blood removed, and primary cell cultures of the anterior pituitary lobe (AL) were investigated. Analyses were performed using immunohistochemistry, RT-PCR, and cytokine-specific bioassays. RESULTS:Stress stimulation by a novel environment increased NF-IL6-immunoreactivity (IR) in the pituitary´s perivascular macrophages and hypothalamic paraventricular cells and a rise in Tb lasting approximately 2h. LPS stimulation lead to NF-IL6-IR in several additional cell types including ACTH-IR-positive corticotrope cells in vivo and in vitro. Two other proinflammatory transcription factors, namely signal transducer and activator of transcription (STAT)3 and NFkappaB, were significantly activated and partially colocalized with NF-IL6-IR in cells of the AL only after LPS-stimulation, but not following psychological stress. In vitro NF-IL6-activation was associated with induction and secretion of TNFalpha in folliculostellate cells, which could be antagonized by the JAK-STAT-inhibitor AG490. CONCLUSIONS:We revealed, for the first time, that NF-IL6 activation occurs not only during inflammatory LPS stimulation, but also during psychological stress, that is, a novel environment. Both stressors were associated with time-dependent activation of NF-IL6 in different cell types of the brain and the pituitary. Moreover, while NF-IL6-IR was partially linked to STAT3 and NFkappaB activation, TNFalpha production, and ACTH-IR after LPS stimulation; this was not the case after exposure to a novel environment, suggesting distinct underlying signaling pathways. Overall, NF-IL6 can be used as a broad activation marker in the brain and might be of interest for therapeutic approaches not only during inflammatory but also psychological stress.
Keywords: Nuclear factor interleukin-6 Lipopolysaccharide; Pituitary; Tumor necrosis factor alpha; Hypothalamic paraventricular nucleus; ddc:610